The intrinsically disordered amino-terminal region of human RecQL4: multiple DNA-binding domains confer annealing, strand exchange and G4 DNA binding. Issue 20 (21st October 2014) - Keller, Heidi; Kiosze, Kristin; Sachsenweger, Juliane; Haumann, Sebastian; Ohlenschläger, Oliver; Nuutinen, Tarmo; Syväoja, Juhani E.; Görlach, Matthias; Grosse, Frank; Pospiech, Helmut
Abstract: Human RecQL4 belongs to the ubiquitous RecQ helicase family. Its N-terminal region represents the only homologue of the essential DNA replication initiation factor Sld2 of Saccharomyces cerevisiae, and also participates in the vertebrate initiation of DNA replication. Here, we utilized a random screen to identify N-terminal fragments of human RecQL4 that could be stably expressed in and purified from Escherichia coli . Biophysical characterization of these fragments revealed that the Sld2 homologous RecQL4 N-terminal domain carries large intrinsically disordered regions. The N-terminal fragments were sufficient for the strong annealing activity of RecQL4. Moreover, this activity appeared to be the basis for an ATP-independent strand exchange activity. Both activities relied on multiple DNA-binding sites with affinities to single-stranded, double-stranded and Y-structured DNA. Finally, we found a remarkable affinity of the N-terminus for guanine quadruplex (G4) DNA, exceeding the affinities for other DNA structures by at least 60-fold. Together, these findings suggest that the DNA interactions mediated by the N-terminal region of human RecQL4 represent a central function at the replication fork. The presented data may also provide a mechanistic explanation for the role of elements with a G4-forming propensity identified in the vicinity of vertebrate origins of DNA replication.